The Robustness of Cellular Immunity Determines the Fate of SARS-CoV-2 Infection - Moga, Esther; Lynton-Pons, Elionor; Domingo, Pere (Frontiers in Immunology, 2022)
Two years after the appearance of SARS-CoV-2 virus, the causal agent of the current global pandemic, it is time to analyze the evolution of immune protection that infection and vaccination provide us. Cellular immunity plays an important role in limiting disease severity and resolution of infection. The early appearance, breadth and magnitude of SARS-CoV-2 specific T cell response has been correlated with disease severity. Thus, it has been observed that T cell responses may be sufficient to clear infection with minimal disease in COVID-19 patients with X-linked or autosomal recessive agammaglobulinemia. However, the knowledge about the phenotypic and functional diversity of CD8+ cytotoxic lymphocytes, CD4+ T helper cells, mucosal-associated innate T (MAIT) cells and CD4+ T follicular helper (TFH), which play a critical role in infection control as well as long-term protection, is still evolving. It has been described as the CD8+ cytotoxic lymphocytes interrupt viral replication by secreting antiviral cytokines (IFN-γ and TNF-α)and directly killing infected cells, negatively correlating with stage of disease progression. Also CD4+ T helper cells have been reported to be key pieces leading, coordinating and ultimately regulating antiviral immunity. For instance, in some more severe COVID-19 cases a dysregulated CD4+ T cell signature may contribute to the greater production of pro-inflammatory cytokines responsible for pathogenic inflammation. Here we discuss how cellular immunity is the axis on which the rest of the immune system components spin around considering it orchestrates and leads the antiviral response by regulating inflammatory cascade and, as a consequence, the innate immune system as well as promoting a correct humoral response through of CD4+ TFH cells. This review also analyses the critical role of cellular immunity modulating the development of high-affinity neutralizing antibodies and germinal center B cell differentiation into memory and long-lived antibody secreting cells. Finally, since currently in certain countries there is a high percentage of vaccinated population and even in some cases vaccine booster doses are being administered we also summarize the newer approaches about long-lasting protective immunity and cross-protection of cellular immune response against SARS-CoV-2.